Isolation of Pseudobutyrivibrio ruminis and Pseudobutyrivibrio xylanivorans from rumen of Creole goats fed native forage diet - Grilli, Diego Javier (2013)
We isolated and identified functional groups of bacteria in the rumen of Creole goats involved in ruminal fermentation of native forage shrubs. The functional bacterial groups were evaluated by comparing the total viable, total anaerobic, cellulolytic, hemicellulolytic, and amylolytic bacterial counts in the samples taken from fistulated goats fed native forage diet (Atriplex lampa and Prosopis flexuosa). Alfalfa hay and corn were used as control diet. The roll tubes method increased the possibility of isolating and 16S rDNA gene sequencing allowed definitive identification of bacterial species involved in the ruminal fermentation. The starch and fiber contents of the diets influenced the number of total anaerobic bacteria and fibrolytic and amylolytic functional groups. Pseudobutyrivibrio ruminis and Pseudobutyrivibrio xylanivorans were the main species isolated and identified. The identification of bacterial strains involved in the rumen fermentation helps to explain the ability of these animals to digest fiber plant cell wall contained in native forage species.